(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This paper is a pragma-rhetorical analysis of a speech given by a member of the English Royal Family with the goal of convincing the reader of their point of view. Persuasion can be thought of as the process of swaying the decision-making process of another individual toward a specific option or line of action via the use of arguments or reasons, as well as by the use of appeals to both feeling and intellect. Additionally, it can be thought of as the act of swaying the minds of others through the use of arguments or reasons. (Cherry,2022). This study addresses how one member of the royal family deploys successfully the pragmarhetorical strategies to persuade the people about the sincerity of his stance. To this end, this paper ventures on analyzing Prince Harry’s speech of secession from the Royal Family